2024
DOI: 10.1002/adsc.202301082
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocyclic Carbene Organocatalyzed [3+3] Annulation for the Enantioselective Synthesis of Benzopyranothiazinones

Karina Mroczyńska,
Zbigniew Rafiński

Abstract: The design, inspired by the core‐structure of oxicam has allowed the enantioselective synthesis of benzopyranothiazinone motifs employing N‐heterocyclic carbene (NHC) catalysis. The NHC‐mediated transformation involves the reaction of α,β‐unsaturated aldehydes with suitable substituted benzothiazinone derivatives. This process encompasses the initial formation of α,β‐unsaturated acylazoliums from ynals and concurrent generation of enolates from benzothiazinone. The culmination of these reactions results in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…Recently, we demonstrated that the bioisosteric 1,2-benzothiazinone 1,1-dioxide system, in reaction with ynals, undergoes a stereoselective transformation into tricyclic benzopyrano-thiazinones with high enantioselectivity under NHC catalysis. 8…”
mentioning
confidence: 99%
“…Recently, we demonstrated that the bioisosteric 1,2-benzothiazinone 1,1-dioxide system, in reaction with ynals, undergoes a stereoselective transformation into tricyclic benzopyrano-thiazinones with high enantioselectivity under NHC catalysis. 8…”
mentioning
confidence: 99%